The Relationship Between Parental Attachment and the Independence of College Students Living Away From Home - Putri, Najwa Aulia; Taufik, Taufik (The Future of Education Journal, 2025)
This research is motivated by regional students who are transitioning from high school to college who have to migrate away from their families, which is a critical phase in early adulthood development that can trigger various psychological and social challenges. This phenomenon is caused by, among other things, students who have to migrate away from their parents with the double challenge of needing to adapt to more complex academic demands while developing independence in the context of physical separation from their inherent figure (parents). This study aims to describe  student parental attachment and student independence, and determine the relationship between parental attachment and regional student independence. This study uses a quantitative method with a correlational descriptive approach. The research sample totaled 60 first-year BK FIP UNP 2024 regional students who were selected using the total sampling technique. The instruments used were  in the form of parental attachment questionnaires and independence questionnaires. The data were analyzed using descriptive analysis techniques and tested using the Pearson Product Moment correlation formula. The results of the study showed that: (1) the average  parental attachment  achievement score of regional students reached (77.14%) most regional students had  high parental attachment, (2) the average score of regional student independence achievement reached (81.06%) most regional students had high independence, and (3) there was a significant positive relationship between parental attachment with the independence of first-year regional students with a correlation of 0.621.